Advances in the use of MOFs for cancer diagnosis and treatment: An overview - Abuçafy, Marina Paiva [UNESP]; da Silva, Bruna Lallo [UNESP]; Junior, João Augusto Oshiro [UNESP]; Manaia, Eloisa Berbel [UNESP]; Chiari-Andréo, Bruna Galdorfini; Armando, Renan Augusto Marson [UNESP]; Frem, Regina Célia Galvão [UNESP]; Chiavacci, Leila Apare-Cida [UNESP] (Bentham Science Publishers, 2020)
Nanoparticles as drug delivery systems and diagnostic agents have gained much attention in recent years, especially for cancer treatment. Nanocarriers improve the therapeutic efficiency and bioavailability of antitumor drugs, besides providing preferential accumulation at the target site. Among different types of nanocar-riers for drug delivery assays, metal-organic frameworks (MOFs) have attracted increasing interest in the academic community. MOFs are an emerging class of coordination polymers constructed of metal nodes or clusters and organic linkers that show the capacity to combine a porous structure with high drug loading through distinct kinds of interactions, overcoming the limitations of traditional drug carriers explored up to date. Despite the rational design and synthesis of MOFs, structural aspects and some applications of these materials like gas adsorp-tion have already been comprehensively described in recent years; it is time to demonstrate their potential applications in biomedicine. In this context, MOFs can be used as drug delivery systems and theranostic platforms due to their ability to release drugs and accommodate imaging agents. This review describes the intrinsic characteristics of nanocarriers used in cancer therapy and highlights the latest advances in MOFs as anticancer drug delivery systems and diagnostic agents. to characteristics.
Keywords: Cancer diagnosis; Cancer theranostics; Cancer therapy; Drug delivery; Metal-organic frameworks; Nanocarriers